Bioreactors : analysis and design - Panda, Tapobrata (McGraw-Hill's AccessEngineering., 2011)
"In recent times, the field of Biology has seen many changes and advancements. This evolution makes a good knowledge about the bioreactor and its operation inevitable for all professionals and students working in this area. Bioreactors: Analysis and Design, arguably the first of its kind, will address all the issues faced by this group. The book begins with an overview of biological reactions, elements of bioreactor design, and fundamentals of mass and energy balances in biological reactions. It discusses in detail the important bioreactors, viz., air-lift reactor, reactors for animal cell processes, and reactors for plant cell processes. Also, CFD in bioreactors is discussed and numerous numerical problems are provided throughout for better explanation of the processes. The book also covers the mechanical design considerations for the various kinds of bioreactors. With its comprehensive coverage, this book would be useful for researchers, teachers, and students working in the area of bioreactors alike.".